Tindak Tutur Ekspresive dalam Novel My Oxford Year Karya Julia Whelan - Izwa Camila Putri (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This study aims to describe the forms and functions of expressive speech acts used by the main character, Eleanor Durran, in My Oxford Year by Julia Whelan. This study employed a descriptive qualitative method with a pragmatic approach. The data consisted of Eleanor's utterances containing expressive speech acts collected from the dialogues in the novel and were analyzed based on their forms and functions. The findings reveal that expressive speech acts in the novel are realized in two forms: direct speech acts and indirect speech acts. Both forms are found in declarative, interrogative, and imperative sentence structures. In addition, the study identifies five functions of expressive speech acts, namely expressing gratitude, surprise, fear, panic, and anger. These functions reflect Eleanor's psychological state and emotional responses to the various events she experiences throughout the story. The findings also indicate that expressive speech acts play an important role in conveying the character's emotions, building interpersonal relationships, and supporting character development within the narrative. Furthermore, this study is expected to contribute to pragmatic studies, particularly those concerning expressive speech acts in literary works.